2020
DOI: 10.1016/j.celrep.2020.108226
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Variation of the Dengue Virus 2 Genotypes Impacts the Neutralization Activity of Human Antibodies in Vaccinees

Abstract: SUMMARY Dengue virus (DENV) infects an estimated 390 million people each year worldwide. As tetravalent DENV vaccines have variable efficacy against DENV serotype 2 (DENV2), we evaluated the role of genetic diversity within the pre-membrane (prM) and envelope (E) proteins of DENV2 on vaccine performance. We generated a recombinant DENV2 genotype variant panel with contemporary prM and E isolates that are representative of global genetic diversity. The DENV2 genotype variants differ in growth kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“…DENV homotypic reinfection, reported in people in Nicaragua and Peru, is potentially driven by genotype differences between primary and secondary infecting viruses 17,18,87 . Some studies have demonstrated that antigenic variation of genotypes can have a high impact on the breadth of antibody neutralization against different genotypes elicited by immune sera from people who have been exposed to natural infections or vaccination 88 . Petty et al and Shrestha et.al., demonstrated that monoclonal antibody panels generated against DENV1 genotype II and DENV2 Southeast Asia genotypes have lower neutralizing efficacy against heterotypic genotypes of the same serotypes 89,90 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DENV homotypic reinfection, reported in people in Nicaragua and Peru, is potentially driven by genotype differences between primary and secondary infecting viruses 17,18,87 . Some studies have demonstrated that antigenic variation of genotypes can have a high impact on the breadth of antibody neutralization against different genotypes elicited by immune sera from people who have been exposed to natural infections or vaccination 88 . Petty et al and Shrestha et.al., demonstrated that monoclonal antibody panels generated against DENV1 genotype II and DENV2 Southeast Asia genotypes have lower neutralizing efficacy against heterotypic genotypes of the same serotypes 89,90 .…”
Section: Discussionmentioning
confidence: 99%
“…DENV vaccine development is complicated by four antigenically diverse serotypes (DENV 1-4) and their intra-serotype (genotype) diversity at both local and global scales [14][15][16] . Several studies have reported the association between the genotype shift and magnitude of the outbreak and disease severity [17][18][19][20][21][22] . However, data on circulating genotype level information is limited in India.…”
Section: Introductionmentioning
confidence: 99%
“…DENV differs significantly among its four serotypes in terms of immune recognition, and antibodies that neutralize a specific serotype do not provide long-term immunity against distinct DENV serotypes (Sabin, 1952). Moreover, the four DENV serotypes differ with >6% variation at the genotype level (Shrivastava et al, 2018), and studies suggest that this natural variation within the genotypes has an impact on vaccine efficacy (Gallichotte et al, 2018b;Juraska et al, 2018;Martinez et al, 2020;Rabaa et al, 2017). In addition to natural genotypic variation, DENV virion maturation is known to play a role in altering neutralizing antibody responses to fusion loop-specific antibodies (Raut et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, certain genotypes from DENV1 for example cluster closer antigenically to certain genotypes from DENV2 (Katzelnick et al, 2015). The intra-serotypic genetic variation that exists within each serotype may explain the variable vaccine efficacy through differential recognition of close and distant strains compared with the vaccine antigen strain (Figure 1) (Gallichotte et al, 2018b;Martinez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The DENV presents mainly four different serotypes antigenically, DENV1-DENV4. Infections with any of the DENV serotypes may result in disease, which is primarily characterized by high fevers, severe joint and muscle pain, and rash ( 4 ). At worse, if patients suffer a second infection with another serotype, they may result in severe disease such as DHF and DSS, which are accompanied by thrombocytopenia, vascular leakage, and hypotension thus may result in death ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%